Microwave sintering of mullite–cordierite precursors prepared from solution combustion synthesis. Issue 8 (September 2015) - Nikzad, L.; Ghofrani, S.; Majidian, H.; Ebadzadeh, T.
Abstract: Mullite–cordierite composite was synthesized using the solution combustion synthesis method and glycine as a fuel and aluminum nitrate, magnesium nitrate and colloidal silica as the reagents. The effect of fuel to oxidizer ratio on the combustion behavior, as well as chemical composition and morphology of the formed powders was investigated. All synthesized powders were amorphous with submicron particle size. It was found that the change of fuel to oxidizer ratio had no effect on synthesis of this composite without heat treatment. The smallest particle size of composite powder was obtained as 302 nm for ratio less than 1 (rich of fuel). Mullite, cordierite and spinel were detected after microwave heating at 1200 and 1400 °C. Mullite and cordierite were detected as the only crystalline phases when the stoichiometric ratio of fuel to oxidizer was chosen and this composite obtained the highest density of 2.61 g/cm 3 .